REVIVALISME ISLAM VERSUS NASIONALISME ARAB: MEMBANDING PEMIKIRAN DAN GERAKAN POLITIK SAYYID QUTHB - GAMAL ABDUL NASSER - Hamdan Hamdan (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2018)
This study aims to track and find the point of equality and point of difference between the two Islamic political figures in Egypt. Sayyid Quthb is known as the Islamic Revivalism and Gamal Abdul Nasser as a national Arabic figure. The exploration is done through the library. The equation of these two figures is their movement appear as resistance (reaction) to Western Imperialism. The difference, through Islamic revivalism, Quthb wants the application of Islam as the basis or principles of politics life. While through Arab nationalism, Nasser more wishes the implementation of the principal of nationalism, and religion as an instrument to achieve the goal.